Always reforming? : Nurturing a church for human rights in South Africa - Palm, Selina (Stellenbosch Theological Journal, 2018)
This article explores the post-apartheid call to South African churches to play an ongoing theological role in the shared task of building a human rights culture for all. It seeks a counter-hegemonic human rights praxis that emphasises the lack of a human rights culture and turns to the early insights of German Reformed theologian Jürgen Moltmann on human rights realisation. This points to an important task for local congregations today. It places this in conversation with current South African empirical realities to argue for a theological disruption of the power-laden imagery underpinning much human rights abuse. It concludes that a liberating Trinitarian praxis for human rights can shape a transformational ecclesiology that speaks to concerns raised by South African church youth within a local church today with a history of struggle involvement. Their voices offer a challenge to churches to be "always reforming" on human rights concerns.